2019
DOI: 10.24018/ejbmr.2019.4.5.82
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strategic Positioning on Organizational Performance of Independent Power Producers in Rwanda A Case Study of Selected IPPs

Abstract: The purpose of this study was to investigate the effect of strategic positioning on organizational performance of Independent Power Producers in Rwanda with a case study of selected IPPs. Moreover this study sought to determine the effects of differentiation strategy, costing and promotion strategy, perceived quality of service as well as pricing strategy on the performance of selected IPPs in Rwanda.  The related literature review was discussed on the theoretical review on positioning theory, Industrial organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Results reported showed that focus strategy elements, that is, pricing, costing and service quality strategies are enhanced performance. To the contrary, findings of differentiation have negative outcome on performance of organizations (Mukeshimana, Nkechi & Jefferson, 2019).…”
Section: Focus Strategies and Performancementioning
confidence: 93%
See 3 more Smart Citations
“…Results reported showed that focus strategy elements, that is, pricing, costing and service quality strategies are enhanced performance. To the contrary, findings of differentiation have negative outcome on performance of organizations (Mukeshimana, Nkechi & Jefferson, 2019).…”
Section: Focus Strategies and Performancementioning
confidence: 93%
“…The results of the current research revealed that differentiation strategies affect positively and significantly performance of pharmaceutical companies in Rwanda. However, the findings of the research of Mukeshimana, Nkechi and Jefferson (2019) found it otherwise because they found that differentiation have negative outcome on performance of organizations.…”
Section: Source: Field Data (2022)mentioning
confidence: 99%
See 2 more Smart Citations
“…Although positioning by quality and price has generally been found to relate strongly with market performance (Blankson et al, 2008), only a handful of studies have been done in Rwanda (Mukeshimana et al, 2019); besides a few studies have specifically examined whether positioning strategy has sales and customer retention benefits claimed (Chang et al, 2015;Kalafatis, 2000;Blankson & Crawford, 2012). The significance of positioning strategy cannot be overemphasised though since; empirical evidence shows that no one positioning strategy achieves results in all situations (Saqib, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%